Pattern of antibiotic use for acute respiratory infections among out-patients in South Asian Region: Protocol for a systematic review. Issue 4 (29th January 2021) - Al-Amin, Saif; Hassan, Md Zakiul; Saif-Ur-Rahman, K.M.; Chowdhury, Muhammad Abdul Baker; Morrison, Sharon D.; Donevant, Sara B.; Chowdhury, Fahmida
Abstract: Background: South Asian region has been experiencing the increasing burden of antimicrobial resistance (AMR) primarily due to over and irrational prescribing of antibiotics. Acute respiratory infections (ARIs) are the leading cause of out-patients' visits in the region. Despite commonly known viral aetiology, ARI is the single largest reason for antibiotic prescriptions contributing the exponential growth of AMR in the region. Collated data on antibiotic consumption for ARI at outpatients and resistance pattern of respiratory pathogen are lacking in the region. Methods: MEDLINE, Cochrane, CINAHL Plus (EBSCO), and Web of Science will be searched for eligible papers. Titles and abstracts, and full texts of the relevant studies will be screened by 2 independent reviewers against the inclusion criteria. Data extraction and quality of the studies will be assessed by 2 reviewers independently using the JBI Critical Appraisal Tools. A third reviewer will resolve any disagreement at any point between 2 reviewers. Results: The review will assess proportions of ARI patients receiving antibiotic therapy and types of antibiotics prescribed among outpatients of all ages in South Asia. This review will also assess the pattern of antimicrobial resistance among respiratory pathogens causing ARI in the region. Conclusions: This systematic review will evaluate published literature, summarize the existing data on the antibiotic prescribing patterns for outpatients with ARI in South Asia. The holistic finding of the proportion of patients receiving antibiotic therapy for ARI, proportion of different types of antibiotic received, and resistance against respiratory pathogen might guide future research. This underscores a need for formulating regional and national policy for AMR mitigation strategy, and revising clinical practice guidelines for the clinician to ensure rational use of antibiotics for ARI. PROSPERO: registration no: CRD42018116658